2007
DOI: 10.1029/2006pa001382
|View full text |Cite
|
Sign up to set email alerts
|

Response of California Current forcing to mid‐Holocene insolation and sea surface temperatures

Abstract: [1] We find that mid-Holocene insolation causes systematic changes in wind forcing of the California Current system, suppressing wind stress in the spring and enhancing wind stress in the summer and autumn. Both largeand regional-scale processes play an important role in the insolation enhancement of wind stress, with elevated summer insolation magnifying both large-scale sea level pressure gradients and regional-scale land-sea thermal contrast. We find that prescribed changes in large-scale sea surface temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…RegCM3 has been used extensively to study the potential response of regional climate to anthropogenic increases in greenhouse forcing [e.g., Ashfaq et al , 2009; Diffenbaugh et al , 2005; Gao et al , 2008; Gao and Giorgi , 2008; Seth et al , 2007; Trapp et al , 2007; White et al , 2006]. The RegCM3 performance over the contiguous United States has been detailed in a number of previous studies [e.g., Diffenbaugh et al , 2006; Diffenbaugh and Ashfaq , 2007; Rauscher et al , 2008; Walker and Diffenbaugh , 2009]. For this study, RegCM3 data are obtained from simulations with a domain covering the contiguous United States at 25 km horizontal grid spacing and 18 levels in the vertical, with initial and lateral boundary conditions provided by the NASA Finite Volume General Circulation Model (FVGCM) [ Atlas et al , 2005].…”
Section: Methodsmentioning
confidence: 99%
“…RegCM3 has been used extensively to study the potential response of regional climate to anthropogenic increases in greenhouse forcing [e.g., Ashfaq et al , 2009; Diffenbaugh et al , 2005; Gao et al , 2008; Gao and Giorgi , 2008; Seth et al , 2007; Trapp et al , 2007; White et al , 2006]. The RegCM3 performance over the contiguous United States has been detailed in a number of previous studies [e.g., Diffenbaugh et al , 2006; Diffenbaugh and Ashfaq , 2007; Rauscher et al , 2008; Walker and Diffenbaugh , 2009]. For this study, RegCM3 data are obtained from simulations with a domain covering the contiguous United States at 25 km horizontal grid spacing and 18 levels in the vertical, with initial and lateral boundary conditions provided by the NASA Finite Volume General Circulation Model (FVGCM) [ Atlas et al , 2005].…”
Section: Methodsmentioning
confidence: 99%
“…The interaction between atmospheric circulation (the Aleutian Low and North Pacific High) and northeast Pacific sea surface temperature produce climate variations that drive large-scale variations in the composition and distribution of terrestrial ecosystems in CSC (Namias and Cayan, 1981;Trenberth and Hurrell, 1994;Harrison, 2003;Diffenbaugh and Ashfaq, 2007). Strong correlations between marine and continental records from coastal northern California and Oregon have shown that the response time of the two regions to changes in millennial scale climate forcing is similar, and that oceanographic conditions on these time scales have a direct impact on coastal climates (Pisias et al, 2001).…”
Section: Paleoclimate Change In Coastal Southern California and Offshmentioning
confidence: 99%
“…Cooling of late Holocene SSTs in the Santa Barbara Basin (SBB) has been attributed to a stronger influence of the California Current during the spring, which likely caused an increase in spring upwelling (Barron and Bukry, 2007;Diffenbaugh and Ashfaq, 2007). In particular, the Neogloquadrina pachyderma isotope data reflect the penetration of cool waters of the California Current into the SBB during the spring, leading to greater diatom (opal) productivity Kennett et al (2007).…”
Section: Santa Barbara Basinmentioning
confidence: 99%